2021
DOI: 10.1096/fj.202100406r
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes comparison of IVF/ICSI among different trigger methods for final oocyte maturation: A systematic review and meta‐analysis

Abstract: During the in vitro fertilization treatment, human chorionic gonadotrophin (hCG) is routinely used as a substitute for the natural endogenous LH surge during the final stage of oocyte maturation. However, it does not provide the FSH surge observed in the mid‐cycle of the natural cycle. To date, whether the FSH surge can improve oocyte quality and pregnancy outcomes remains unknown. Randomized controlled trials comparing the following four trigger methods to conventional hCG were examined: GnRH agonist (GnRHa),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The difference in LH levels between the two groups was therefore considered acceptable. Concerning the trigger types, a recent meta-analysis that included both the GnRH agonist and the dual trigger versus the hCG found no significant difference in pregnancy rate ( 28 ). The number of oocytes retrieved was reported to be significantly higher with the dual trigger than hCG alone.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in LH levels between the two groups was therefore considered acceptable. Concerning the trigger types, a recent meta-analysis that included both the GnRH agonist and the dual trigger versus the hCG found no significant difference in pregnancy rate ( 28 ). The number of oocytes retrieved was reported to be significantly higher with the dual trigger than hCG alone.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not consider the effect of different triggers on the results; however, because it has been reported that there is no difference in the number of oocytes retrieved between hCG and GnRH agonist triggers, it is thought that there is no effect on OSI. 56 , 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not consider the effect of different triggers on the results; however, because it has been reported that there is no difference in the number of oocytes retrieved between hCG and GnRH agonist triggers, it is thought that there is no effect on OSI. [56][57][58] This is the first study to develop an individualized dosing algorithm for gonadotropins in Japanese patients. Further accumulation of cases is required to develop a standardized calculator that can be used throughout Japan.…”
Section: Ta B L Ementioning
confidence: 99%
“…However, Gao et al’s retrospective study and Eftekhar et al’s RCT reported that the number of oocytes retrieved and embryos available were both higher in the dual-trigger group than the hCG trigger-alone group. A 2021 systematic review and meta-analysis similarly found that the two trigger methods were equally effective in terms of pregnancy rate [ 30 ]. At variance with the findings of our study, another meta-analysis reported that although the number of mature oocytes or fertilized oocytes retrieved and the ongoing pregnancy rate were similar, the CPR with dual-trigger was significantly higher than hCG trigger alone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%